To determine the shatter and tumbler strength of given raw material (Iron ore, Lime stone) - Rao, Lakkoju Sankara (Main Library, IIT (BHU), Varanasi, 2022)
To determine the shatter and tumbler strength of given raw material (Iron ore, Lime stone) (a) This video gives the introduction of Shatter Index and Tumbler Index testing equipment (b) Shows the procedure of finding the Shatter and Tumbler Index. PART 1 Introduction to Shatter & Tumbler Strength Equipment and Procedure PART 2 Shatter Index Test PART 3Tumbler Test PART 4Results